AB0318 Patient acceptable symptom state (pass) in rheumatoid arthritis. (23rd January 2014) - Covelli, M.; Rotondo, C.; De Marino, A.V.; Lanciano, E.; Notarnicola, A.; Rinaldi, A.; Montinaro, C.; Lapadula, G.
Abstract : Background: In clinical trials, Patient Reported Outcomes (PROs) are playing an increasingly important role to quantify functional and pain improvements from the patients' viewpoint. The Patient Acceptable Symptom State (PASS) is a PRO and is defined as a qualitative measure of a patient well-being. Objectives: 1) PASS estimation in rheumatoid arthritis patients. 2) Considering the satisfied patients group (PASS yes), assessment of cut-off points for the following clinimetric indices: patient Global Assessment (pzGA); physician Global Assessment (phGA) and joint pain intensity (VAS pain). 3) Assessment of the association between the groups determined by the pzGA, phGA and VAS pain cut-off points and the disease activity levels defined by the composite indices (DAS, SDAI, CDAI, PAS). Methods: 225 rheumatoid arthritis patients (age 55.45±13.6 years, disease duration 12.9±9.04 years, BMI 25.8±5.07 kg), in biologics treatment. For each patient, clinimetric and composite indices were evaluated; each patient was also asked to answer the following yes/no (PASS) question "Taking into account all your daily life activities, your pain level and your functional impairment, do you consider your current state satisfactory?".The PASS cut-off points were calculated as the 75th centile of the values obtained for the self-reported satisfactory condition patients (Tubach's method 1 ). The association between the groups defined by the new pzGA, phGA and VAS pain cut-off points and the disease activity levels determined by the DAS, SDAI, CDAI, PAS composite indices was estimated using the γ statistics. Statistical differences between any two subgroups were evaluated by means of either the Mann-Whitney U-test or the Student's Test, where appropriate. The chi-square test and Fischer's exact Test were used to compare categorical variables and proportions. Results: 1) 75.2% of patients were satisfied of their state. The disease activity level, assessed using DAS ‡, SDAI ‡ and CDAI ‡, was low for the satisfied group (PASS yes) and moderate for the unsatisfied group (PASS no) ( ‡ =p<0.000). 2) The PASS cut-off points obtained are 50 mm for pzGA, 30 mm for phGA and 40 mm for VAS pain. Satisfied patients with pzGA, phGA, VAS pain score less than or equal to the cut-off point were in remission according to the DAS *, in low disease activity according to the SDAI † and CDAI ‡ indices. On the contrary, satisfied patients with score greater than the PASS cut-off points proved in moderate disease activity according to the DAS *, SDAI † and CDAI ‡ indices (*, †, ‡ p<0.0001). 3) The association between the groups defined by the new pzGA, phGA and VAS pain cut-off points and the disease activity levels determined by DAS (γ=0.85, γ=0.87, γ=0.85, respectively), SDAI (γ=0.90, γ=0.88, γ=0.87 respectively), CDAI (γ=0.89, γ=0.87, γ=0.84 respectively) and PAS (γ=1, γ=1, γ=1 respectively) proved very strong. Conclusions: PASS proves an effective index to assess patients self-reported disease activity levels. In order to implement the cut-off points found in this study, their validation on a wider study group would be required; however, the results found are encouraging. References: F. Tubach, P. Ravaud, G. Baron, et al. Evaluation of clinically relevant states in patient reported outcomes in knee and hip osteoarthritis: the patient acceptable symptom state. Ann Rheum Dis 2005;64:34-37 Disclosure of Interest: None Declared